ETHICAL AWARENESS AND ACADEMIC USE OF AI IN LEGAL AND BUSINESS WRITING AMONG UNDERGRADUATE STUDENTS AT A THAI PUBLIC UNIVERSITY: ETHICAL AWARENESS AND ACADEMIC USE OF AI IN LEGAL AND BUSINESS WRITING AMONG UNDERGRADUATE STUDENTS AT A THAI PUBLIC UNIVERSITY - White, Alan Robert; Darodjat, Tubagus Achmad; Iriantoro, Agung (PENA LAW: International Journal of Law, 2025)
This study examines undergraduate students’ awareness, perceptions, usage patterns, and ethical considerations regarding the use of generative Artificial Intelligence (AI) in legal and business writing. A 20-item questionnaire was administered to assess familiarity with AI tools, beliefs about their usefulness, patterns of use in academic contexts, and views on ethical implications. The results indicate moderate awareness and generally positive perceptions of generative AI, particularly in terms of improving writing quality and clarifying complex concepts. However, actual usage remains limited, and many students report a lack of formal instruction or clear guidelines on ethical use. Notably, students expressed strong support for institutional guidance and recognised the importance of responsible AI integration in academic settings. The findings underscore the need for targeted educational interventions and policy development to align student behaviour with ethical academic standards. Recommendations are made for integrating AI training into business education and conducting further research on the long-term academic effects of generative AI use.